Gender and innovation processes in wheat-based systems - Badstue, Lone B.; Petesch, Patti; Williams, G.; Umantseva, A. (International Maize and Wheat Improvement Center, 2017)
This WHEAT report is based on 43 village case studies from eight countries set in diverse wheat-based farming regions of the Global South.